Ethyl Acetate Fraction of Helianthus tuberosus L. Induces Anti-Diabetic, and Wound-Healing Activities in Insulin-Resistant Human Liver Cancer and Mouse Fibroblast Cells - Arokia Vijaya Anand Mariadoss; SeonJu Park; Kandasamy Saravanakumar; Anbazhagan Sathiyaseelan; Myeong-Hyeon Wang (MDPI AG, 2021)
Traditional, complementary, and integrative medicine are globally accepted alternative methods for the treatment of diabetes mellitus (DM). However, the mechanism of anti-diabetic effects of Helianthus tuberosus L. remains unproven. In the present study, antioxidant and anti-diabetic activity of the tubers of H. tuberosus were studied in detail. Methanolic extracts of H. tuberosus tubers were subjected to solvent fractionation method by increasing the polarity of the solvent using n-hexane, and ethyl acetate. The obtained methanol extracts and its fractions were subjected to free radical scavenging activity (DPPH and ABTS assay) and in vitro enzyme (α-amylase and α-glucosidase) inhibition assay. Moreover, glucose uptake in insulin-resistant HepG2 cell line was analyzed. The preliminary phytochemical analysis confirmed the presence of phenolic and flavonoid compounds in the active fraction. The radical scavenging and in vitro diabetic related enzyme inhibitory activities were found to be dose dependent. The maximum ABTS+ and DPPH scavenging activity was documented in ethyl acetate fraction of the H. tuberosus followed by methanol extract, hexane fraction, and methanol fraction. We also found that H. tuberosus showed a less toxicity in mouse fibroblast cells and enhance the glucose uptake in insulin-resistant HepG2 cells. Besides, the ethyl acetate fraction of the H. tuberosus analyzed by UPLC-QTOF-MS-MS and GC/MS revealed the presence of phenolic compounds such as neochlorogenic acid, chlorogenic acid, caffeic acid, 5-O-(4-coumaroyl)-quinic acid, feruloylquinic acid, caffeoylquinic acid, isoxazolidine, salicylic acid β-D-glucoside, dicaffeoylquinic acid isomers, salvianolic acid derivative isomers, and 1,4 dicaffeoylquinic acid etc. Among the identified phytochemicals, six were chosen for molecular docking study to explore their its inhibitory interactions with α-amylase and α-glucosidase. Taken together, the findings of the present study suggested that phytocompounds of EAF were responsible for the significant in vitro antioxidant, wound-healing, and anti-diabetic activities.